2016
DOI: 10.1093/bja/aev399
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of three transducer orientation approaches for ultrasound guided internal jugular venous cannulation

Abstract: Background: Ultrasound-guided internal jugular venous access increases the rate of successful cannulation and reduces the incidence of complications, compared with the landmark technique. Three transducer orientation approaches have been proposed for this procedure: short-axis (SAX), long-axis (LAX) and oblique-axis (OAX). Our goal was to assess and compare the performance of these approaches. Methods: A prospective randomized clinical trial was conducted in one teaching hospital. Patients aged 18 yr or above,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 20 publications
1
96
0
Order By: Relevance
“…After duplicated literature search results were excluded, and the topics and abstracts of the articles were examined, we reviewed the full texts of 20 articles. Ultimately, 7 publications that involved 802 participants were included in our analyses (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After duplicated literature search results were excluded, and the topics and abstracts of the articles were examined, we reviewed the full texts of 20 articles. Ultimately, 7 publications that involved 802 participants were included in our analyses (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials reported information on the first‐pass success rate and were included in this meta‐analysis (Figure , Table ). We chose a random‐effects model to evaluate the RRs for overall effect size for the 3 examined techniques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,[34][35][36][37] Unfortunately the in-plane ultrasound technique is technically demanding and a change to this technique may represent an unrealistic expectation given the training burden it would represent. 38 The pragmatic recommendation is therefore to ensure that training in internal jugular cannulation does not present ultrasound-guidance as a panacea, but recognises and attempts to mitigate the potential for harm when using this technology in different ways.…”
Section: Attitudes To Risk When Using Ultrasoundmentioning
confidence: 99%